YESUS DALAM PRAINKARNASI - Eko Sugiyarto (Alucio Dei, 2020)
When we try to know God deeply, we quickly realize the limitations of the mind we have. There is no mortal being, who can completely understand God. Understanding of God will be manifested in the Person of Jesus as a human being today is still a study considering there are still some parties who cannot accept that. The God from whom allthings come is said to have existed before the world was made, He is eternal and unlimited. So the pre-incarnation or pre-existence of Jesus is to show that Jesus existed before all things were made. He is not limited by time, He is never absent, because He is eternal. Thus Jesus in the Preincarnation is showing that Jesus is entirely God. It existsand exists in every moment. Proof of Jesus' existence in the pre-incarnation is presented in the Old Testament scriptures. Many verses of God's Word show us that Jesus existed before the foundation of the world. He is with His people and chosen people